The IFRS option to reclassify financial assets out of fair value in 2008: the roles played by regulatory capital and too-important-to-fail status - Fiechter, Peter; Landsman, Wayne R.; Peasnell, Kenneth; Renders, Annelies (Review of Accounting Studies, 2017)
Amendment of IAS 39 by the IASB in 2008 provided an option to reclassify investments from fair value to historical cost. We predict that too-important-to-fail (TITF) banks took less advantage of this option because the political protection they enjoyed insulated them from regulatory pressure. Banks that did not enjoy this protection had greater reason to make use of this option since doing so would protect their Tier 1 capital. As predicted, findings reveal that TITF banks made less use of the reclassification option to protect their Tier 1 capital and there is a significant moderating influence of TITF status on the incentive to reclassify investments for banks with lower regulatory capital. This finding is consistent with TITF banks placing less weight on protecting regulatory capital and thereby retaining flexibility to sell assets. Our findings provide evidence that accounting choices are affected by the importance of banks to their economies.